PARTISIPASI MASYARAKAT DALAM PELAKSANAAN PENDIDIKAN SEKOLAH DASAR DI KECAMATAN SILOKARNO DOGA KABUPATEN JAYAWIJAYA PROVINSI PAPUA - WANTIK, MARKUS; RURU, JOORIE; MAMBO, RULLY (Sam Ratulangi University, 2020)
The purpose of this research is to learn how to divide the community in the implementation ofprimary school education in the Silokarno Doga District, Jayawijaya Regency This study used descriptivequalitative method. Community participation can be seen from the four dimensions of participation ineducation, namely the degree of participation, participation initiatives, organizational participation, andattitudes in participation. Informants of the study are the principal of the school, head of the primaryschool board, village head, community / religious leaders, and parents of elementary school students. .Data collection uses interviews, while the analysis technique used is interactive model analysis. Theresults showed: (1) The degree of community participation in supporting elementary school education wasstill low, both in terms of providing support, support from personnel and material contributions.Associated with supporting education is still limited to a small part of the community namely communityleaders, religious leaders, traditional leaders, and some parents of students. (2) Initiatives of communityparticipation in supporting the implementation of school education based on spontaneous and persuasiveare still low in the general population, not good enough for community / religious / adat leaders, and forsome parents of students at the school. (3) Organizations supporting the community in supporting theimplementation of primary school education are still low both individuals and groups. (4) Communityassistance programs that support education are also still low such as in terms of supporting, supporting,or supporting programs determined by the school or school institution.Keywords: Community Participation, Implementation of Basic Education